The mechanism of wear elements coupler device of rolling stock - Артемчук, В.В. (Problems of Tribology, 2014)
The paper presents the results of investigations into the mechanism of wear elements coupler device of rolling stock. It is shown that the elements of the coupler are several types of wear, and their combination. Shock surface casing coupler is most exposed to the collapse, fatigue and abrasive wear, and often their simultaneous action. The studies can define the search direction of wear-resistant materials that will improve the turnaround of locomotives and wagons.